STUDY OF THE DEPENDENCIES BETWEEN THE CONTRAST OF THE TARGET ON A CONDITIONALLY HOMOGENEOUS BACKGROUND AND THE PROBABILITY OF COMPLETING THE FIRING TASK - Pistriak, Petro; Kushnariov, Bohdan; Radionov, Hennadii (Honor and Law, 2023)
The process of performing a firing task is detailed and, based on the conducted research, the dependences between the contrast of the target on a conditionally homogeneous background and the probability of performing the firing task are determined and given. he contrast of the target (target) with the background in the range from 1 to 0,5 has almost no effect on the object detection time and is up to 2 seconds. Targets painted in such a contrast to the background can be used for military personnel in the first months of service, training in target reconnaissance and during preparatory firing exercises. Using contrast on the background in the range from 0,5 to 0,2 significantly increases the time to detect the target, and leads to its almost complete invisibility. Such a contrast is advisable to be used during shooting exercises by experienced shooters and for use at short distances. For a specified (previously established or constant) time to perform the exercise, the contrast of the target with the background should not be lower than 0,4. Otherwise, it is impractical to set a clear time for target detection and, accordingly, for the execution of the shooting exercise. The conducted calculations and studies also indicate a decrease in the probability of target detection depending on the contrast on a conditionally homogeneous background, the range to the target, the observation sector and the shooter's personal experience. For further stages of training with the aim of gradually acquiring the skills of performing fire tasks, there is a need to develop a scientific and methodological apparatus for determining the conditions of the exercise, taking into account the current level of training of the shooter. At the same time, the components of shooting training exercises can be the number of targets, observation sector, angular dimensions, target contrast, terrain background, etc., which will depend on the time of the firing task.